The Role of Microglia in Alzheimer’s Disease From the Perspective of Immune Inflammation and Iron Metabolism - Long, Hui-Zhi; Zhou, Zi-Wei; Cheng, Yan; Luo, Hong-Yu; Li, Feng-Jiao; Xu, Shuo-Guo; Gao, Li-Chen (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD), the most common type of senile dementia, includes the complex pathogenesis of abnormal deposition of amyloid beta-protein (Aβ), phosphorylated tau (p-tau) and neuroimmune inflammatory. The neurodegenerative process of AD triggers microglial activation, and the overactivation of microglia produces a large number of neuroimmune inflammatory factors. Microglia dysfunction can lead to disturbances in iron metabolism and enhance iron-induced neuronal degeneration in AD, while elevated iron levels in brain areas affect microglia function. In this paper, we firstly discuss the role of microglia in AD and then introduce the role of microglia in the immune-inflammatory pathology of AD. Their role in AD iron homeostasis is emphasized. Recent studies on microglia and ferroptosis in AD are also reviewed. It will help readers better understand the role of microglia in iron metabolism in AD, and provides a basis for better regulation of iron metabolism disorders in AD and the discovery of new potential therapeutic targets for AD.